2021
DOI: 10.3233/jpd-202521
|View full text |Cite
|
Sign up to set email alerts
|

Non-Genetic Risk Factors for Parkinson’s Disease: An Overview of 46 Systematic Reviews

Abstract: Background: Numerous systematic reviews (SRs) and meta-analyses on non-genetic risk factors for Parkinson’s disease (PD) development have been published with inconsistent conclusions. Objective: This overview of SRs aimed to summarize evidence on non-genetic factors for the development of PD from the published SRs, and explore the reasons behind the conflicting results. Methods: Three international databases were searched for SRs with meta-analyses summarized evidence on non-genetic factors for PD development.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 87 publications
(147 reference statements)
0
22
0
3
Order By: Relevance
“…The disease results in a considerable burden for patients as well as insurance and social costs [4,5]. Similar to dementia, diagnosing the disease early is important in order to improve care [6] or even intervene preventatively [7,8]. As a result, early and prodromal symptoms have been the focus of considerable research over the last 20 years [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…The disease results in a considerable burden for patients as well as insurance and social costs [4,5]. Similar to dementia, diagnosing the disease early is important in order to improve care [6] or even intervene preventatively [7,8]. As a result, early and prodromal symptoms have been the focus of considerable research over the last 20 years [6,9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, it has been hypothesized that the association between exposure to environmental toxins such as pesticides and PD risk might be affected by CYP2D6 gene variants. In this regard, exposure to pesticides has been demonstrated to potentially modify the effect of CYP2D6 variants on PD risk [ 116 ]. It has also been shown that the poor metabolizer genotype of CYP2D6 is associated with a higher DNA methylation status [ 53 ].…”
Section: Environmental Impact On Epigenetic Modifications In Pdmentioning
confidence: 99%
“…In addition, case-control studies often suffer from selection bias at study entry (13,18,39). Selection bias could, for instance, occur in case-controls studies investigating the association of diet with PD (40). If controls are selected on the basis of an advertisement about research on nutrition, usually this will attract people who have an interest in this topic and who already have a healthy diet (18,41).…”
Section: Importance Of Population-based Studies In Pre-diagnostic Parkinson's Diseasementioning
confidence: 99%